Genetic Testing for Diagnosis of Hypertrophic Cardiomyopathy Mimics: Yield and Clinical Significance. (April 2020) - Hoss, Sara; Habib, Manhal; Silver, Josh; Care, Melanie; Chan, Raymond H.; Hanneman, Kate; Morel, Chantal F.; Iwanochko, Robert M.; Gollob, Michael H.; Rakowski, Harry; Adler, Arnon
Abstract : Background: Genetic testing is helpful for diagnosis of hypertrophic cardiomyopathy (HCM) mimics. Little data are available regarding the yield of such testing and its clinical impact. Methods: The HCM genetic database at our center was used for identification of patients who underwent HCM-directed genetic testing including at least 1 gene associated with an HCM mimic ( GLA, TTR, PRKAG2, LAMP2, PTPN11, RAF1, and DES ). Charts were retrospectively reviewed and genetic and clinical data extracted. Results: There were 1731 unrelated HCM patients who underwent genetic testing for at least 1 gene related to an HCM mimic. In 1.45% of cases, a pathogenic or likely pathogenic variant in one of these genes was identified. This included a yield of 1% for Fabry disease, 0.3% for familial amyloidosis, 0.15% for PRKAG2 -related cardiomyopathy, and 1 patient with Noonan syndrome. In the majority of patients, diagnosis of the HCM mimic based on clinical findings alone would have been challenging. Accurate diagnosis of an HCM mimic led to change in management (eg, enzyme replacement therapy) or family screening in all cases. Conclusions: Genetic testing is helpful in the diagnosis of HCM mimics in patients with no or few extracardiac manifestations. Adding these genes to all HCM genetic panels should be considered. Abstract : Supplemental Digital Content is available in the text.